2019
DOI: 10.3390/su11061809
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aesthetic Preferences in Relation to Vegetation-Created Enclosure in Chinese Urban Parks: A Case Study of Shenzhen Litchi Park

Abstract: Building on the mystery/complexity/legibility/coherence model of Kaplan and Kaplan (1989) and up-to-date landscape visualization techniques, this paper presents a case study analyzing people’s aesthetic preferences for scenes with varying levels of enclosure created through vegetation. Participants were asked to view 48 computer-generated urban park scenes with different levels of enclosure and to rate them for three aesthetic preference factors: coherence, complexity, and legibility. The results are as follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
(55 reference statements)
0
22
0
Order By: Relevance
“…Open spaces like Fig. 6 or enclosed spaces create different effects on visual and encourage diverse aesthetic experiences (Liu and Schroth, 2019). This planting scene is the highest rating because it is highly visible, wellstructured and provides a pleasant view (Liu and Schroth, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Open spaces like Fig. 6 or enclosed spaces create different effects on visual and encourage diverse aesthetic experiences (Liu and Schroth, 2019). This planting scene is the highest rating because it is highly visible, wellstructured and provides a pleasant view (Liu and Schroth, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Principles and objectives that landscape designers and planners have been applying for the last several hundred years support the implication that coherence and complexity are essential to creating landscapes that people like (Kuper, 2017). Later, Liu and Schroth, (2019) conducted a survey where coherence, complexity and legibility are rated high for open landscape scene.…”
Section: The Objective Paradigm In Perceiving Landscape Aestheticmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have shown that dense woodland with shrubbery understory receives low acceptance from the public [11,42,44], while open spaces are positively correlated with preferences [45]. In studies evaluating the impact of enclosure space on three aesthetic preference factors (i.e., coherence, complexity, and legibility) [46], the participants rated legibility and complexity for physically enclosed scenes lower than for physically open scenes.…”
Section: Safety-related Environmental Characteristics and Preferencesmentioning
confidence: 97%
“…Preference studies usually test for direct effects that include the impact of environmental characteristics on preference (e.g., [38,57,74]) or on the factors that build such a preference. For example, in the Liu and Schroth [46] study testing the impact of physical and visual accessibility (as components of the situations defining permeability of enclosure) on preferences, this effect was measured on three variables that belong to the basic determinants of preferences [35]: coherence, complexity, and legibility.…”
Section: The Mediating Role Of Safety In the Relationship Between Envmentioning
confidence: 99%